2022
DOI: 10.3390/antiox11112168
|View full text |Cite
|
Sign up to set email alerts
|

ApoE3 vs. ApoE4 Astrocytes: A Detailed Analysis Provides New Insights into Differences in Cholesterol Homeostasis

Abstract: The strongest genetic risk factor for sporadic Alzheimer’s disease (AD) is the presence of the ε4 allele of the apolipoprotein E (ApoE) gene, the major apolipoprotein involved in brain cholesterol homeostasis. Being astrocytes the main producers of cholesterol and ApoE in the brain, we investigated the impact of the ApoE genotype on astrocyte cholesterol homeostasis. Two mouse astrocytic cell lines expressing the human ApoE3 or ApoE4 isoform were employed. Gas chromatography–mass spectrometry (GC-MS) analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…Notably, some of the current results resemble the data reported by our group in a previous study focused on cholesterol homeostasis in ApoE4 astrocytes. Indeed, we have demonstrated that Ts2 mice, in comparison to Eu mice, show HMGCR, DHCR24, and cholesterol trends similar to those already observed in ApoE4 astrocytes compared to ApoE3 [29]. However, we must take into account that the two experimental models are different.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Notably, some of the current results resemble the data reported by our group in a previous study focused on cholesterol homeostasis in ApoE4 astrocytes. Indeed, we have demonstrated that Ts2 mice, in comparison to Eu mice, show HMGCR, DHCR24, and cholesterol trends similar to those already observed in ApoE4 astrocytes compared to ApoE3 [29]. However, we must take into account that the two experimental models are different.…”
Section: Discussionmentioning
confidence: 73%
“…The limited expression of HMGCR and DHCR24 and lower cholesterol content in our Ts2 mouse model and ApoE4 astrocytes [29] imply meaningful issues about the pharmacological treatment of AD-like neurodegeneration with the use of lipid lowering agents, in particular statins which are HMGCR inhibitors. Although the effects of statins are mainly at the systemic level, these drugs, in particular the lipophilic simvastatin which appears the most effective at crossing the BBB, are proposed as neuroprotective in the early stages of AD thanks to their hypocholesterolemic activity, and antioxidant and anti-inflammatory properties [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from being the main APOE producers in the brain, astrocytes alongside microglia are crucial for the uptake and endocytosis of substrates from the extracellular space including Aβ, tau and α-synuclein [123]. Aβ uptake/clearance in astrocytes is facilitated via lipid-associated endocytic receptors such as LDLR or LRP1 and has been shown to occur via APOE isoform-dependent complex binding, with -POE2/Aβ and APOE3/Aβ complexes resulting in faster clearance than APOE4/Aβ complexes in the mouse brain [124][125][126]. Indeed, reduced LRP1 expression and Aβ uptake in astrocytes was linked to receptor entrapment in the EEs due to late APOE4 receptor dissociation in the EE, an effect that was counteracted through inhibition of nuclear histone deacetylation 4 (figure 2, parts 2-4) [127].…”
Section: (A) Astrocytesmentioning
confidence: 99%
“…Astrocytes are more efficient than neurons at cholesterol production as they contain copious precursors for cholesterol synthesis (Nieweg et al., 2009). Astrocyte‐derived cholesterol upregulates Aβ production (Wang et al., 2021) and produces apolipoprotein E (APOE) as cargo carriers supplying cholesterol esters to neurons via LRP1 and LDLR (low density lipoprotein receptor) (Staurenghi et al., 2022). Brain cholesterol is continuously being shed from the plasma membrane by transporters ABCG1/ABCG5 and ABCA1, the ATP binding cassette subfamily A member 1 (Koldamova et al., 2014), and is metabolized by CYP46A1, the cholesterol 24(S)‐hydroxylase in neurons to 24(S)‐hydroxycholesterol.…”
Section: Introductionmentioning
confidence: 99%